SURVEY IN A WATER RESOURCE MANAGEMENT PROJECT OF AN UNDERGROUND RIVER IN INDONESIA - VETTER, GÜNTER SCHMITT; MARTIN (Boletim de Ciências Geodésicas, 2006)
The district of Gunung Kidul in the Yogyakarta Special Province in middle Java is known as one of the poorest regions in Indonesia. One of the essential reasons is the acute water scarcity during the dry season. This karst area is composed of hundreds of networked caves. Due to these cave structures there is a total exchange of the surface run off and an infiltration through wide branched underground flow systems. Since 2003 the Federal Ministry of Education and Research (BMBF), Germany, is funding an interdisciplinary pilot project at the University of Karlsruhe comprising a water resources management in one of the caves, Gua Bribin. The basic idea is a partial damming up of the underground water flow by means of a barrage with an integrated micro hydro power plant. The main objective of the project is a strongly increased water supply of the population combined with a general improvement of the living conditions especially in the dry season. The paper describes, in addition to the interdisciplinary aspects of the project, the geodetic contribution, the surveying work and the data processing. The single topics are the basic survey for the installation of the drilling and the underground construction site, the control measurements for the vertical drilling of the shaft of 100 m depth, the surveying of the cave geometry in detail (1,5 km length) and the presentation of the cave within a three dimensional model as the basis for further applications such as navigation through the cave, simulation of constructions, special calculations (for example profiles and volumes) etc. The paper ends with an outlook to a new project under application concerning a comprehensive water resources management in the whole region, in the frame of a new research funding program of the BMBF.